Pengaruh keputusan adopsi cloud computing dari segi kerangka teknologi, organisasi, dan lingkungan terhadap Kinerja UMKM - Rianita Puspa Sari; Aditia Ayu Rahma Nabila; Aulia Fashanah Hadining; Deri Teguh Santoso (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The existence of Industry 4.0 has a disruptive impact on the economic sector, which results in a complex level of competition. Anticipating this, the Indonesian government launched making Indonesia 4.0 in an effort to improve the performance and competitiveness of the national industry. One of the priorities is Micro, Small and Medium Enterprises (MSMEs), because MSMEs are the backbone of the economic sector in Indonesia. On the other, MSMEs have a number of constraints in the form of limited capital and costs, lack of infrastructure and facilities, lack of work networks, inadequate human resources in the field of business and low use of information technology, which makes it difficult to compete. Therefore, MSMEs need information technology solutions that meet their needs. Adoption of cloud computing is one of the information technologies that is a solution for MSMEs to be able to improve their performance towards a better direction so that they can be competitive. The adoption of cloud computing in MSMEs has several consideration factors that are seen from the aspect of TOE. The purpose of this study, in the form of analysis of decision factors from the aspect of TOE in the adoption of cloud computing to the performance of MSMEs in Karawang Regency, using the SEM-PLS method with 100 samples of MSMEs. The results of this study indicate that the aspects of TOE affect cloud computing adoption and MSME performance, while cloud computing adoption does not affect the performance of MSMEs.